Lipid components of bile increase the protective effect of conjugated bile salts against antifungal drugs - Hsieh, Shih-Hung; Brock, Matthias (Elsevier, 2017)
Fungi and bacteria can persist in the human gall bladder. Previous studies have shown that bile protects Candida albicans in this cryptic host niche from antifungals, providing a reservoir for intestinal re-colonization after discontinuation of antifungal therapy. Bile and conjugated bile salts trap antifungals in micelles, thereby reducing their bioavailability and possibly promoting the development of drug resistance. Here we show that the protective effect of bile and conjugated bile salts is not limited to C. albicans, but also observed with other fungi. Interestingly, bile, but not conjugated bile salts conferred resistance of C. albicans against fluconazole and only bile mediated resistance of Aspergillus terreus against voriconazole. To investigate this higher potency of bile we aimed in a step-wise reconstitution of bile from conjugated bile salts. Neither addition of phospholipids nor saturated fatty acids protected from azoles. In contrast, supplementation with polyunsaturated fatty acids increased azole resistance and decreased the critical micelle concentration of conjugated bile salts to the level of bile. Therefore, polyunsaturated fatty acids are vital for mixed micelle formation with high potential to trap antifungals. As biliary infections are difficult to treat, drug efficacy in the biliary system should be tested by using reconstituted synthetic bile.